Characterisation of nuclear sub-structures - Patel, S; Patel, Shailendra Bhanubhai (1984)
﻿ When living cells are lysed in non-ionic detergents and 2M NaCl, structures are released that resemble nuclei, termed nucleoids. Nucleoids contain tenaciously attached DNA, RNA and protein. The nature of the interactions of these components is poorly understood. It is known that the DNA is attached to these structures in a looped configuration, and newly synthesised DNA is found closely associated with the attachment sites. Therefore, the speculation that these attachment sites have a functional signification other than for structural purposes has been seriously considered. To investigate these possibilities, the proteins were characterised for DNA binding activity, and the presence of any enzymatic activity. Some of the nucleoid proteins are derived from the cell surface, and specific phosphorylating and methylating activities were also detected. The significance of these findings remains to be determined. The study of the DNA-binding activity is hampered by the fact that these proteins are not readily solubilised away from the nucleic acids. However, DNA-binding proteins are present in nucleoids. No specificity for DNA sequences was demonstrable, using the protein blotting technique. In the course of these studies, a new technique was devised to enable sequence-binding proteins to be identified. Examination of the DNA close to thl attachment sites shows it to be enriched in transcriptionally active genes, and in a given population of cells, some genes are closer to the attachment sites than others. This supports the idea that genes are specifically arranged within the nucleus of any cell, and that this position is of functional significance. Direct examination of the most closely adherent DNA to these structures did not reveal any one DNA sequence that may mediate attachment.